Financing global Development: The BRICS New Development Bank - Stephany Griffith-Jones (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
The UN Conference on Financing for Development in Addis Ababa in July 2015 will pave the way for the implementation of the post-2015 development agenda. The Briefing Paper series “Financing Global Development“ analyses key financial and non-financial means of implementation for the new Sustainable Development Goals (SDGs) and discusses building blocks of a new framework for development finance. The BRICS New Development Bank (NDB) was created in mid-2014 by the governments of Brazil, Russia, India, China and South Africa. It will have a fairly large capital contribution – initially of US 50 billion – from BRICS countries and can grow up to 100 billion with contributions from other countries. It will fund in-vestment in infrastructure and sustainable development on a significant scale. The NDB will provide valuable resources to help fill the massive gap in investment in infrastructure and sustainable development resources in emerging and developing economies, which has been estimated to reach at least US 1 trillion annually. It will also give emerging and developing countries a greater voice in the development finance architecture. Other emerging economies are also creating institutions. Thus, BRICS leaders have also created new institutions, such as the Contingency Reserve Arrangements (CRA), in BRICS countries to provide official liquidity in times when balance of payments adjustments are needed. Furthermore, with China's initiative, the Asian Infrastructure Investment Bank (AIIB) is being created. It will have 57 potential member countries, including all major European economies (such as Germany, the United Kingdom and France), with the largest share of the capital being contributed by China. China also announced the creation of the New Silk Road Bank to fund investment in infrastructure connections within Asia as well as those linking to Europe and Africa. The creation of these new institutions contributes in a valuable way to the aims of financing sustainable development, as will be discussed in the Financing for Development conference in Addis Ababa on 12–16 July 2015.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Internationales Finanzsystem